Behaviour of lactose with the presence of lactic acid and Ca as affected by pH. Issue 4 (2nd October 2017) - Chandrapala, Jayani; Gauthier, Claire; Vasiljevic, Todor
Abstract : Contradictory statements about the effects of pH change on crystallisation behaviour of lactose exist in the literature. Considering the importance of addressing the processability issue of acid whey, a systematic study is required to establish lactose crystallisation behaviour in the presence of LA and Ca at concentrations present in real acid whey waste streams emphasising impact of pH. Structural modifications of lactose were evident at elevated, more neutral pH in the presence of 1% w/w LA and 0·12% w/w Ca. These structural changes led to changes in the anomeric equilibrium of lactose, which manipulated the water–lactose behaviour and increased the crystallinity. Therefore, altering pH to 6·5 may be the solution to proper industrial processing of acid whey, enhancing the ability of lactose to crystallise properly.